The Role Of The Teacher As Class Manager In Increasing Spiritual Intelligence Through The Implementation Of Classic Values - Umi Jariyah; Mujiburrohman; Meti Fatimah (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2024)
This study aims to determine the role of the teacher as class manager in increasing spiritual intelligence. Corcerning with the objective of the study, the writer uses descriptive qualitative methods. The subjects of the study were 7 teachers who teach in MIM Bendo special program. The Data collection techniques by using interviews, observation and documentation. Meanwhile, the data validation technique uses triangulation. Furthermore, the data analysis uses data reduction, data presentation, and drawing conclusions. The results of this study indicate that the teacher's role as classroom manager can improve students' spiritual intelligence through moral development strategies, moral studies, congregational prayers, Al-Quran learning, and Ramadhan Islamic boarding schools activities. Due to these steps, teachers can improve students' spiritual intelligence through fostering faith and morals. On the other hand, the obstacles in increasing students' spiritual intelligence are such as a curriculum that focuses on academic aspects, lack of understanding and support, time constraints, differences in beliefs and values, and personal disobedience. To overcome these obstacles, teachers can take steps such as revising the curriculum, holding additional training, integrating spiritual values in learning, respecting students' different beliefs, and involving parents. Implementation of the teacher's role as class manager can be done.